2005
DOI: 10.1002/lsm.20269
|View full text |Cite
|
Sign up to set email alerts
|

Photoablation of inner limiting membrane and inner retinal layers using the Erbium:YAG‐laser: An in vitro study

Abstract: Background and Objectives: To explore the potential of Er:YAG-laser irradiation for precise and tractionless retinal tissue and inner limiting membrane ablation. Materials and Methods: We used free-running Er:YAGlaser irradiation (l ¼ 2.94 mm) transmitted either through a 10 cm long low-OH-quartz fiber or a 2 m long sapphire fiber that produced a more homogenous light distribution at the fiber tip. Retinal ablation in porcine retinal explants was performed under air or perfluorodecaline (PFD). Ablation depth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…13,[17][18][19][20][21][22][23] However, our contact-mode mid-IR microsphere scalpel can create spatially small ablation craters below the limit of current intraocular fiber delivery systems, while using a less powerful laser source. Sapphire microspheres with a refractive index of 1.71, used as lenses, focus laser light at the sphere's surface, creating a robust contact laser device whose performance is unaffected by the transmission medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[17][18][19][20][21][22][23] However, our contact-mode mid-IR microsphere scalpel can create spatially small ablation craters below the limit of current intraocular fiber delivery systems, while using a less powerful laser source. Sapphire microspheres with a refractive index of 1.71, used as lenses, focus laser light at the sphere's surface, creating a robust contact laser device whose performance is unaffected by the transmission medium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the Er:YAG laser during vitrectomy procedures have been reported by D'Amico, Joseph, and Hoerauf. 13,[18][19][20][21][22][23] These studies did not use contact probes but fibers and devices at varying distances from retinal and membrane tissue with spot sizes greater than 100 μm.…”
Section: Erbium:yag Laser For Tissue Ablationmentioning
confidence: 99%
“…The thickness of the ILM is thinnest at the fovea region of the retina. However, the thickness is larger at the posterior pole of retina (Hoerauf et al, 2006). Furthermore, the ILM is also present over the retinal blood vessels.…”
Section: Discussionmentioning
confidence: 96%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]32 However, our contact mode mid-IR microsphere scalpel can create spatially small ablation craters below the limit of current intraocular fiber delivery systems, while using a less powerful laser source. Sapphire microspheres with a refractive index of 1.71, used as lenses, focus laser light at the sphere's surface creating a robust contact laser device where the transmission medium will not affect the device's performance.…”
Section: Discussionmentioning
confidence: 99%
“…Over 20 years ago, the erbium:YAG laser was identified as a promising candidate for precise surgery [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] due to strong water absorption in soft tissues at its emission wavelength of λ ¼ 2.94 μm. However, this laser did not gain widespread acceptance in vitreoretinal surgery due to its relatively large size, slow rate of tissue cutting, and necessity for bulky and exotic flexible mid-infrared (IR) delivery systems.…”
Section: Introductionmentioning
confidence: 99%